Cranial osteology of the genus Sclerurus (Passeriformes: Furnariidae) - Guzzi, Anderson; Duarte Branco, Mario Sergio; Donatelli, Reginaldo Jose [UNESP] (Revista De Biologia Tropical, 2016)
The Furnariidae encompasses 293 species and has been recognized as an example of continental adaptive radiation. They inhabit biomes from deserts to humid forests at all strata and show morphological heterogeneity unparalleled among birds at any taxonomic level. Sclerurus is a uniform genus of cryptic, mainly dark brown furnariids, with short black tails which are found solitary on or near the ground inside humid forest. The aim of the present study was to describe and to compare the cranial osteology of all six Sclerurus species (S. scansor, S. mexicanus, S. guatemalensis, S. caudacutus, S. rufigularis, and S. albigularis) to identify osteological characters that are (1) unique to each species, (2) shared among species, and (3) that are exclusive to the genus when compared to other members of Furnariidae. For this, bone structures and measurements were done following standard methodologies. The results showed that Sclerurus differs from other Furnariidae in the following characteristics: a narrowed caudal portion of the nostril with a more rounded shape allowing upper's jaw greater mobility, used when foraging on soft substrates; the development of the post-orbital process may be related to digging behavior, as the presence of a short parsphenoid rostrum projection, a reduced cerebellar prominence, and the tapered caudal portion of the nostrils. Among the species, the interorbital width is larger in S. caudacutus and S. rufigularis, than in the remaining species. The development of the post-orbital process may be related to the behavior of digging nests in earthen banks; the narrowing of the caudal portion of the nostril allows for the greater mobility of the superior maxilla, which is used by Sclerurus when foraging in soft substrates on forest grounds.
Keywords: Ovenbirds; Scleruridae; anatomy; systematic